Deficiency of 60 to 70S RNA in Murine Leukemia Virus Particles Assembled in Cells Treated with Actinomycin D - Levin, Judith G. (1974)
Production of particles with the ultrastructural appearance of C-type virions persisted for at least 6 h in actinomycin D-treated cells infected with murine leukemia virus. This phenomenon occurred despite severe inhibition of viral RNA synthesis. Virus particles present in a 6-h harvest sedimented in sucrose gradients with the buoyant density characteristic of RNA tumor viruses (1.16 g/cm(3)) and exhibited high levels of reverse transcriptase activity in response to the exogenous template polyriboadenylic acid·oligo deoxythymidylic acid in the range of untreated controls. However, RNase-sensitive endogenous activity was only ⅕ the level found in controls. This observation correlated with a marked reduction in infectivity. Kinetic studies on the appearance of labeled RNA in banded virions revealed that within the first hour after addition of actinomycin D, particles contained 60 to 70S RNA and two low-molecular-weight RNA species corresponding to 8 and 4S RNA. After approximately 1 h of incubation with actinomycin D, 60 to 70S RNA could not be detected and 4S RNA was the predominant species. These findings suggest that murine leukemia virus particles assembled in the presence of actinomycin D are deficient in 60 to 70S viral RNA.